THE USE OF QUIZZIZ TO FACILITATE STUDENTS’ VOCABULARY LEARNING (Universitas Stikubank (UNISBANK) Semarang, 2022)
Quizziz is an educational application download that contains an online quiz and can be used in multiplayer. This application can be accessed via the web or can also be downloaded from the Play Store or Appstore on a smartphone. Its use is also very easy and practical. So it is possible to use it as a test, homework, or small quiz in the teaching and learning process. This research discusses about the implementation of Quizziz as a teaching media to facilitate students’ learning vocabulary for Grade X at MA NU 1 Limpung in the academic years of 2022/2023. The study aims to determine : ( 1) This is to determine of using Quizziz Application on Teaching-Learning Vocabulary in students who have difficulty in learning.( 2 ) This is to determine the effect of using Quizziz to motivate students in the teaching-learning vocabulary. ( 3 ) To discover differences between students' after using Quizziz in learning vocabulary.The researchers utilized descriptive qualitative research methodologies in this study. The data obtained shows that Quizziz can motivate students’ in the teaching learning vocabulary process.